Influence of Phi (Φ) Shaped in Circular Ring Inserts on Thermal Performance in Circular Tube Heat Exchanger: CFD Study - Kandpal, Gaurav; Singh, Satyendra; Bisht, Shubham; Kharkwal, Himanshi (Journal of Graphic Era University, 2023)
<p class="noindent" style="text-align: justify; color: #000000; font-family: ’Times New Roman’; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Enhancement of heat exchangers with the usage of inserts which creates turbulence in fluid flow by enhancing heat transfer rate which is an appealing area for researchers to develop efficient and compact heat exchanger with low expenses. Present work deals with computational investigation on circular tube with <span id="MathJax-Element-2-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: normal; line-height: normal; font-size: 16px; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; position: relative;" tabindex="0" role="presentation" data-mathml="ϕ"><span id="S0.SSx1.p1.m1" class="math" style="transition: none 0s ease 0s; display: inline-block; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.671em;"><span style="transition: none 0s ease 0s; display: inline-block; position: relative; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.61em; height: 0px; font-size: 16.48px;"><span style="transition: none 0s ease 0s; display: inline; position: absolute; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; clip: rect(1.095em, 1000.61em, 2.309em, -999.997em); top: -1.939em; left: 0em;"><span id="MathJax-Span-5" class="mrow" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;"><span id="MathJax-Span-6" class="mi" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; font-family: MathJax_Math-italic;">ϕ<span class="MJX_Assistive_MathML" style="top: 0px; left: 0px; clip: rect(1px, 1px, 1px, 1px); user-select: none; position: static; padding: 0px; border: 0px; height: 1px !important; width: 1px !important; overflow: hidden !important; display: inline; transition: none 0s ease 0s; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;" role="presentation"> shaped circular ring inserts taken as enhancer for better experience in heat transfer. The geometric dimensions of insert are 68 mm outer diameter with inner ring is half of outer diameter concentric ring having varying DR of 0.8, 0.85 and 0.9 with varying PR 3, 4 & 5 in which hydraulic diameter is 68.1 mm. The length of test section is 1500 mm with 1000 W/m<span id="MathJax-Element-3-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: normal; line-height: normal; font-size: 16px; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; position: relative;" tabindex="0" role="presentation" data-mathml="2"><span id="S0.SSx1.p1.m2" class="math" style="transition: none 0s ease 0s; display: inline-block; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.428em;"><span style="transition: none 0s ease 0s; display: inline-block; position: relative; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.428em; height: 0px; font-size: 16.48px;"><span style="transition: none 0s ease 0s; display: inline; position: absolute; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; clip: rect(-0.058em, 1000.43em, 1.156em, -999.997em); top: -0.968em; left: 0em;"><span id="MathJax-Span-8" class="mrow" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;"><span id="MathJax-Span-9" class="msup" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;"><span style="transition: none 0s ease 0s; display: inline-block; position: relative; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.428em; height: 0px;"><span id="MathJax-Span-10" class="mi" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;"><span id="MathJax-Span-11" class="mn" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; font-size: 11.6514px; font-family: MathJax_Main;">2<span class="MJX_Assistive_MathML" style="top: 0px; left: 0px; clip: rect(1px, 1px, 1px, 1px); user-select: none; position: static; padding: 0px; border: 0px; height: 1px !important; width: 1px !important; overflow: hidden !important; display: inline; transition: none 0s ease 0s; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;" role="presentation">2 of regular heat flux is applied and Re ranges from 3000 to 21000. <p class="indent" style="text-align: justify; text-indent: 1em; color: #000000; font-family: ’Times New Roman’; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">CFD analysis conducted, compared & results are presented where maximum augmentation of heat transfer could be obtained 5.02–11.21 times simultaneously TPF is 2.14–3.54 times as compared to smooth tube for inserts with DR 0.8 and PR 3 which attained maximum <span id="MathJax-Element-4-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: normal; line-height: normal; font-size: 16px; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; position: relative;" tabindex="0" role="presentation" data-mathml="<mover accent="true">S˙</mover>"><span id="S0.SSx1.p2.m1" class="math" style="transition: none 0s ease 0s; display: inline-block; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.61em;"><span style="transition: none 0s ease 0s; display: inline-block; position: relative; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.549em; height: 0px; font-size: 16.48px;"><span style="transition: none 0s ease 0s; display: inline; position: absolute; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; clip: rect(-0.179em, 1000.49em, 1.156em, -999.997em); top: -0.968em; left: 0em;"><span id="MathJax-Span-13" class="mrow" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;"><span id="MathJax-Span-14" class="mover" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;"><span style="transition: none 0s ease 0s; display: inline-block; position: relative; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; width: 0.549em; height: 0px;"><span style="transition: none 0s ease 0s; display: inline; position: absolute; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; clip: rect(3.098em, 1000.49em, 4.19em, -999.997em); top: -4.002em; left: 0em;"><span id="MathJax-Span-15" class="mi" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; font-family: MathJax_Main;">S<span style="transition: none 0s ease 0s; display: inline; position: absolute; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; clip: rect(3.158em, 1000.31em, 3.644em, -999.997em); top: -4.305em; left: 0.003em;"><span id="MathJax-Span-16" class="mo" style="transition: none 0s ease 0s; display: inline; position: static; border: 0px; padding: 0px; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none; font-family: MathJax_Main;">˙<span class="MJX_Assistive_MathML" style="top: 0px; left: 0px; clip: rect(1px, 1px, 1px, 1px); user-select: none; position: static; padding: 0px; border: 0px; height: 1px !important; width: 1px !important; overflow: hidden !important; display: inline; transition: none 0s ease 0s; margin: 0px; vertical-align: 0px; line-height: normal; text-decoration: none;" role="presentation">S˙ 3.07–5.1. <p style="text-align: justify; color: #000000; font-family: ’Times New Roman’; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Keywords: Heat exchanger, thermal performance factor, CFD analysis. <h2 id="Sx1" class="h2" style="margin-top: 1.5em; margin-bottom: 1em; color: #000000; font-family: ’Times New Roman’; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Nomenclature